Measurements and Simulations of the Geomagnetically Induced Currents in Low‐Latitude Power Networks During Geomagnetic Storms. Issue 8 (24th August 2020) - Zhang, J. J.; Yu, Y. Q.; Wang, C.; Du, D.; Wei, D.; Liu, L. G.
Abstract: The issue of geomagnetically induced currents (GICs) on large distance ground‐based conductive systems is a global space weather concern nowadays. The low‐latitude power grids are becoming more vulnerable to GICs hazards due to their increasing scale and degree of interconnection. Thus, GICs measurement and modeling in these systems is of great importance. In this study, we present an analysis of the GICs measurement at a Chinese low‐latitude substation during geomagnetic storms. The results show a rough positive correlation between the magnitude of large GIC spikes and d B H /d t spikes. We then built a physical‐based model to simulate the GICs at the low‐latitude substation during storms. It was found that the simulations capture the main active periods of the GICs during the storms with comparative strength of the measurement. This differs from the previous simulation results for high‐latitude regions conducted by Welling et al. (2017; https://doi.org/10.1002/2016SW001505 ). Furthermore, the event analysis method is applied to evaluate the model performance. The results indicate that the physical‐based model is more applicable than the persistence model in the prediction of GICs at low‐latitude power grids during storms. Key Points: GICs measured at a low‐latitude substation during geomagnetic storms are analyzed and simulated The first attempt to model the GICs at a low‐latitude substation during storms by using the physical‐based model The simulations capture the main active periods of GICs with comparable intensity to observations